Periodic, Cross-Kink, and Interaction between Stripe and Periodic Wave Solutions for Generalized Hietarinta Equation: Prospects for Applications in Environmental Engineering - Guangping Li; Jalil Manafian; Mirmehdi Seyyedi; R. Sivaraman; Subhiya M. Zeynalli (Advances in Mathematical Physics)
In the current work, the modified (2 + 1)-dimensional Hietarinta model is considered by employing Hirota’s bilinear scheme. Likewise, the bilinear formalism is obtained for the considered model. In addition, the periodic-solitary, periodic wave, cross-kink wave, and interaction between stripe and periodic wave solutions of the mentioned equation by particular coefficients are offered. The obtained results may be used in the description of the model in fruitful way. Finally, by using the available situations, the physical demeanor of solutions is discussed in the given method. We demonstrated that these solutions validated the program using Maple and found them correct. Moreover, a lot of graphs in some sections to determine the analysis of obtained findings for the aforementioned equation are given. The achieved solutions are also verified by using the Maple software. These periodic wave solutions suggest that these three methods are useful, easy to use, and effective than other methods.